A study of trends in the historical development of elements and techniques related to two-leg systems on the pommel horse - Sano, T.; Watanabe, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The elements of artistic gymnastics have shown a tendency to change over time. Along with such changes in technique, the value of each element will vary. If values that have been historically shared and developed are not recognized, elements and techniques currently in use cannot be understood and the future direction of development cannot be predicted. In order to understand the value associated with gymnastics development, it is necessary to research the historical transition of elements and techniques that has occurred. The evolution of elements and techniques up to around 1970 was described in "Coaching of Artistic Gymnastics" (Kaneko, 1974). Up to the present, however, the historical transition of elements and techniques that has occurred since then has not been thoroughly analyzed. In the present study, therefore, by organizing trends in the historical development of elements and techniques related to the pommel horse, we attempted to clarify the factors that have been involved, in order to provide knowledge that might be useful for developing a systematic theory of gymnastics elements. Our study yielded the following noteworthy points: 1) The 1970s were a period in which a balance existed between the original elements and elements that complicated existing structures. 2) The 1980s were a period that saw a bias towards the complexity of existing structures, such as those that did not possess pommels or flairs. 3) The 1990s were a period that saw bias towards a combination of elements. 4) From 2000 onwards, developments designed to make existing structures more complex were becoming active. 5) The two-legs system in the pommel horse has seen the development of structural complication triggered by original elements that were present in the 1970s. Furthermore, the above-mentioned trends in the development of pommel horse elements have had the following influences: 1) Changes in the shape of the pommel and the adjustment width between the pommels to facilitate support. 2) Changes in technique due to postural simplicity with the intention of achieving maximum amplitude. 3) Changes in the "Code of Points" that emphasize objectivity and the recommendation of high-difficulty value elements.